Predictors of risk of intracerebral haemorrhage in patients with a history of TIA or minor ischaemic stroke. - Ariesen, M; Algra, A; Warlow, C; Rothwell, P (2006)
We developed a model identifying patients with previous cerebral ischaemia at increased risk of intracerebral haemorrhage (ICH). Based on data from eight cohorts, 107 ICHs were found to have occurred among 12 648 patients. Multivariate Cox regression analysis identified the following predictors: age (> or = 60 years, hazard ratio (HR) 2.07), blood glucose level (> or = 7 mmol/l, HR 0.33), systolic blood pressure (> or = 140 mm Hg, HR 2.17), and antihypertensive drugs (HR 1.53). The highest risk quartile was associated with five times more ICHs than the lowest quartile.